2018
DOI: 10.3847/1538-4357/aadadf
|View full text |Cite|
|
Sign up to set email alerts
|

Coexistence of Slow-mode and Alfvén-mode Waves and Structures in 3D Compressive MHD Turbulence

Abstract: The compressible component of solar wind turbulence displays a slow-mode feature. However, the nature of the slow-mode fluctuations remain open. In this work, based on numerical simulations of the driven compressible magnetohydrodynamic (MHD) turbulence with a uniform mean magnetic field, we use polarization of the MHD modes to decompose turbulent velocity and magnetic fields into Alfvén modes, slow modes, and fast modes. The numerical results with different cross-helicity, plasma beta β, and Alfvén Mach numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…For example, characteristics for three separate propagating linear eigenmodes – the Alfvén mode, the slow magnetosonic mode and the fast magnetosonic mode have been studied using numerical simulations (Cho & Lazarian 2002; Kowal & Lazarian 2010; Yang et al. 2018; Makwana & Yan 2020) and observations (Yao et al. 2011; Howes et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, characteristics for three separate propagating linear eigenmodes – the Alfvén mode, the slow magnetosonic mode and the fast magnetosonic mode have been studied using numerical simulations (Cho & Lazarian 2002; Kowal & Lazarian 2010; Yang et al. 2018; Makwana & Yan 2020) and observations (Yao et al. 2011; Howes et al.…”
Section: Introductionmentioning
confidence: 99%
“…A decomposition of the turbulent field is frequently implemented to study different compressible MHD turbulence processes. For example, characteristics for three separate propagating linear eigenmodes -the Alfvén mode, the slow magnetosonic mode and the fast magnetosonic mode have been studied using numerical simulations (Cho & Lazarian 2002;Kowal & Lazarian 2010;Yang et al 2018;Makwana & Yan 2020) and observations (Yao et al 2011;Howes et al 2012;Klein et al 2012). In this work, we decompose the velocity field into solenoidal and compressive parts following Helmholtz decomposition as used in Kida & Orszag (1990, 1992, Miura & Kida (1995), Pan & Johnsen (2017), Wang et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…While fast modes can play an important role in scattering of cosmic rays, simulations have shown that the fast modes might only be a marginal component of compressible turbulence [22]. However, these simulations have been driven incompressively by solenoidal forcing [15,19,[22][23][24]. Thus, a natural question to ask is whether and how the nature of the forcing affects the mode composition of turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…While fast modes can play an important role in scattering of cosmic rays, simulations have shown that the fast modes might only be a marginal component of compressible turbulence. However, these simulations have been driven incompressively by solenoidal forcing [24,[30][31][32]. It is important to identify whether and how changing the nature of the forcing affects the mode composition of turbulence.…”
Section: Pos(icrc2021)038mentioning
confidence: 99%